Терагерцова спектроскопія філаменту для 3D друку - Зайченко, Н. Я. (ХНУРЕ, 2022)
This work is devoted to teraherz spectroscopy in time domain of filament for 3D printing. The relevance of the topic of this study is confirmed by a large number of modern publications on this issue. The subject of research in this paper is the determination of the refractive index of a filament for 3D printing. The scientific novelty consists in taking into account the solidification of the filament during the manufacturing process, the presence of metal impurities, and taking into account the rate of filament supply from the extruder. The practical value lies in the possibility of using recycled materials for processing into filament, thereby solving environmental problems.